Time-Efficient Path Planner in 3D Obstacle-Rich Environments Considering the Maximum Turn Rate of a Fixed-Wing Aerial Vehicle - Jonghoek Kim (Applied Sciences)
A time-efficient path plan algorithm is important for the real-time navigation of a fixed-wing autonomous aerial vehicle in unknown 3D obstacle-rich environments. Note that a fixed-wing aerial vehicle can freely move in 3D environments, not in 2D environments. This research addresses a 3D path planner, which is time-efficient in generating a safe and short path to the destination. In practice, a fixed-wing aerial vehicle has a limited turn rate due to its acceleration limits. The proposed path plan algorithm constructs a smooth 3D path by considering the maximum turn rate of a fixed-wing aerial vehicle. It is proven that the planned 3D path avoids collision with obstacles, while satisfying the turn rate limit constraints. Through computer simulations, one proves the outperformance (low computational load, satisfying maneuverability constraints, and short path length) of the proposed 3D path plan algorithm by comparing it with the state-of-the-art 3D rapidly exploring random tree (RRT)-based path planners considering maneuverability constraints.